2007
DOI: 10.1007/s00253-006-0698-6
|View full text |Cite
|
Sign up to set email alerts
|

Translation elongation factor 1-α gene from Pichia pastoris: molecular cloning, sequence, and use of its promoter

Abstract: The gene encoding translation elongation factor 1-alpha from the yeast Pichia pastoris was cloned. The gene revealed an open reading frame of 1,380 bp with the potential to encode a polypeptide of 459 amino acids with a calculated mass of 50.1 kDa. The potential of the promoter (P (TEF1)) in P. pastoris was investigated with comparison to the glyceraldehyde-3-phosphate dehydrogenase promoter (P (GAP)) by using a bacterial lipase gene as a reporter gene. P (TEF1) demonstrated a tighter growth-associated express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 28 publications
2
26
0
2
Order By: Relevance
“…Its gene was shown to have strong promoter activity in other organisms. The study demonstrated that P TEF1 has a similar capability to produce foreign protein as those produced by P GAP . However, in this study, TGZ expression level of P TEF1 ‐ tgz was lower than that of P FLD1 ‐ tgz , so the recombinant strain under the control of P FLD1 (P FLD1 ‐ tgz ) was selected for subsequent TGZ production.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Its gene was shown to have strong promoter activity in other organisms. The study demonstrated that P TEF1 has a similar capability to produce foreign protein as those produced by P GAP . However, in this study, TGZ expression level of P TEF1 ‐ tgz was lower than that of P FLD1 ‐ tgz , so the recombinant strain under the control of P FLD1 (P FLD1 ‐ tgz ) was selected for subsequent TGZ production.…”
Section: Resultssupporting
confidence: 85%
“…As an inducible promoter, it can be independently induced either by methanol as a carbon source or by methylamine as a nitrogen source . Another promoter, the constitutive translation elongation factor 1‐α promoter (P TEF1 ), has attracted research attention by demonstrating a tighter growth‐associated expression mode and a similar or even greater yield on recombinant protein than glyceraldehyde‐3‐phosphate dehydrogenase promoter (P GAP ), a constitutive promoter that provides a comparable expression level to P AOX1 . P FLD1 and P TEF1 can eliminate the disadvantage related to the use of methanol during the expression of heterologous protein under the control of P AOX1 , thus becoming promising alternative promoters for the expression of foreign protein induced by methylamine or glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…Although several promoters, either constitutive or inducible, are available for this yeast [P AOX1 (8), P AOX2 (9), P FLD1 (10), P DAS (8), P PEX8 (P PER3 ) (11), P YPT1 (12), P GAP (13), P TEF1 (14), P PGK1 (15), P ICL1 (16)], the promoter of the alcohol oxidase I gene ( AOX1 ) has been employed in most studies and applications (1). AOX1 is the predominantly expressed form of two alcohol oxidases ( AOX1 and AOX2 ) in the P. pastoris cell.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the control promoter, much stronger activities of gapdh p (SG) and rpsL p (SG) should be observed. The strong activities of gapdh p and the promoters of various translation elongation factors have also been observed in many other microorganisms, such as fungi, bacteria, micro-algae, and protozoa (Ahmad et al, 2012; Ahn et al, 2007; Hong et al, 2010; Jia et al, 2012; Krasny et al, 2000; Shao et al, 2009; Suarez et al, 2006). …”
Section: Basic Protocol 2 Reconstructing the Silent Nor Gene Clustermentioning
confidence: 82%